The complete nucleotide sequence of the carbapenem resistance-conferring conjugative plasmid pLD209 from a Pseudomonas putida clinical strain reveals a chimeric design formed by modules derived from both environmental and clinical bacteria - Marchiaro, Patricia (2014)
Fil: Marchiaro, Patricia. Universidad Nacional de Rosario. Departamento de Microbiología; Argentina.